2009
DOI: 10.1002/cphc.200800735
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of o‐Nitrobenzaldehyde in the Gas Phase: A New OH. Formation Channel

Abstract: Photolysis of gaseous o-nitrobenzaldehyde (o-NBA) with selected different excitation wavelengths (355-400 nm) is investigated, and the nascent OH radical is detected by the single-photon laser-induced fluorescence (LIF) technique. The relative quantum yield and rotational excitation of OH formation are found to be dependent on the excitation energy. The distributions of rotational, spin-orbit, and Lambda-doublet states are obtained at 355-400 nm by analyzing the experimental data. The OH radicals are found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…These roaming reactions are the lowest accessible pathways for HONO formation on the singlet surface. Formation of ketenes was described earlier by Cheng et al for 2‐nitrobenzaldehyde, though the current case is fundamentally different as we have a ring size reduction. Finally, HPN can also fragment to NO 2 + hydroxyphenyl; this process has a small exit barrier of 7 kJ mol –1 above the products at the M06–2X level of theory, but this TS becomes submerged by 2 kJ mol –1 at the G3SX level of theory, thus suggesting again a barrierless fragmentation as expected for singlet radical–radical interactions.…”
Section: Ground State S0 Pesmentioning
confidence: 53%
See 1 more Smart Citation
“…These roaming reactions are the lowest accessible pathways for HONO formation on the singlet surface. Formation of ketenes was described earlier by Cheng et al for 2‐nitrobenzaldehyde, though the current case is fundamentally different as we have a ring size reduction. Finally, HPN can also fragment to NO 2 + hydroxyphenyl; this process has a small exit barrier of 7 kJ mol –1 above the products at the M06–2X level of theory, but this TS becomes submerged by 2 kJ mol –1 at the G3SX level of theory, thus suggesting again a barrierless fragmentation as expected for singlet radical–radical interactions.…”
Section: Ground State S0 Pesmentioning
confidence: 53%
“…The spectroscopic characteristics of nitrophenols have been studied experimentally , revealing large UV absorption cross sections, ∼10 −17 cm 2 molecule −1 . The photoinduced fragmentation processes in nitrated aromatics are intimately related to the mobility of the H‐atoms and NO x moieties, as is evident from both experimental and theoretical studies . For nitrophenol, the key to the formation of HONO is the aci ‐nitrophenol intermediate ( aci ‐NP ), where the phenolic H‐atom has migrated to the nitro moiety to form a −N(O)OH substituent in up to four possible conformers (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The short formation time for oNBA is in line with DFT computations. 59 Attempts to optimise the structure of the lowest triplet state starting with the ground state geometry ''automatically'' results in a hydrogen transfer to the nitro group. This suggests a barrierless and thereby rapid pathway to the bi-radical.…”
Section: Discussionmentioning
confidence: 99%
“…The phototransformation of o-NBA has been extensively investigated by a number of authors for more than a century because of its photo-reactive property. [6][7][8][9][10][11][12][23][24][25] The first phototransformation study of o-NBA was reported by Ciamician and Silber, 25 which is regarded as the advent of modern organic photochemistry. 26 They observed that, upon photoexcitation, o-NBA undergoes an interesting phototransformation to produce o-nitrosobenzoic acid with the quantum yield of B50% irrespective of the solvent.…”
Section: Introductionmentioning
confidence: 99%